Research on Direction of Arrival Estimation Based on Self-Contained MEMS Vector Hydrophone - Shan Zhu; Guojun Zhang; Daiyue Wu; Xiaoqi Liang; Yifan Zhang; Ting Lv; Yan Liu; Peng Chen; Wendong Zhang (Micromachines, 2022)
A self-contained MEMS vector hydrophone with a scalar–vector integrated design is proposed in this paper. Compared with traditional MEMS vector hydrophones, this design solves the problem of ambiguity in the port and starboard during orientation, and also realizes the self-contained storage of acoustic signals. First, the sensor principle and structural design of the self-contained MEMS hydrophone are introduced, and then the principle of the combined beamforming algorithm is given. In addition to this, the amplitude and phase calibration method based on the self-contained MEMS vector hydrophone is proposed. Then, the sensitivity and phase calibrations of the sensor are carried out in the standing wave tube. The sensitivity of the vector channel is −182.7 dB (0 dB@1 V/<semantics>μ</semantics>Pa) and the sensitivity of the scalar channel is −181.8 dB (0 dB@1 V/<semantics>μ</semantics>Pa). Finally, an outdoor water experiment was carried out. The experimental results show that the self-contained MEMS vector hydrophone can accurately pick up and record underwater acoustics information. It realizes the precise orientation of the target by combining beamforming algorithms. The direction of arrival (DOA) error is within 5° under the outdoor experimental conditions with an SNR of 13.67 dB.